2015
DOI: 10.14692/jfi.11.5.175
|View full text |Cite
|
Sign up to set email alerts
|

Laporan Pertama Infeksi Begomovirus pada Tanaman Mentimun di Bali

Abstract: ABSTRAKTanaman mentimun dengan gejala daun menguning mulai banyak ditemukan pada sejumlah pertanaman mentimun di Desa Apuan dan Desa Bangli, Provinsi Bali. Penyakit ini diduga berasosiasi dengan Begomovirus karena gejalanya mirip dengan infeksi Begomovirus yang dilaporkan terjadi pada tanaman mentimun di Jawa. Selain itu, kutukebul (Bemisa tabaci) ditemukan di lapangan. Penelitian ini bertujuan mengidentifikasi penyebab penyakit daun kuning pada tanaman mentimun. Deteksi dan identifikasi virus dilakukan dengan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
0
7
0
6
Order By: Relevance
“…In addition, the rapid spread of ToLCNDV in Java was facilitated by highly population of its vector Bemisia tabaci on cucumber, especially on underside leaves. Previously, Wiratama et al (2015) reported that the high incidence of ToLCNDV and SLCCNV on cucumber in Bali might due to the high population of B. tabaci. Massive spread of ToLCNDV in cucumber in Java might be also caused by several factors, such as efficient ToLCNDV transmission by B. tabaci with persistent manner (one vector can transmit the virus to healthy plants), either virus or its vector have wide host range, and the presence of weeds surround cultivation area as reservoir plants as previously report by Tiwari et al (2010).…”
Section: Symptoms and Disease Incidence In The Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the rapid spread of ToLCNDV in Java was facilitated by highly population of its vector Bemisia tabaci on cucumber, especially on underside leaves. Previously, Wiratama et al (2015) reported that the high incidence of ToLCNDV and SLCCNV on cucumber in Bali might due to the high population of B. tabaci. Massive spread of ToLCNDV in cucumber in Java might be also caused by several factors, such as efficient ToLCNDV transmission by B. tabaci with persistent manner (one vector can transmit the virus to healthy plants), either virus or its vector have wide host range, and the presence of weeds surround cultivation area as reservoir plants as previously report by Tiwari et al (2010).…”
Section: Symptoms and Disease Incidence In The Fieldmentioning
confidence: 99%
“…It is indicated that the frequency of ToLCNDV and SLCV is very high detected on cucumbers in Java. ToLCNDV was previously reported to infect cucumber in Bali, Central Java, Yogyakarta, and West Java with disease incidence up to 100%, (Septariani et al, 2014;Haerunisa et al, 2016), while until present the existence of Squash leaf curl China virus (SLCCNV) found only in Bali with a disease incidence up to 80% (Wiratama et al, 2015).…”
Section: Symptoms and Disease Incidence In The Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Penyakit daun kuning merupakan salah satu penyakit penting pada tanaman mentimun (Cucumis sativus). Penyakit daun kuning pada mentimun yang berasosiasi dengan Squash leaf curl China virus (SLCCNV) di Bali dilaporkan oleh Wiratama et al (2015) dan Haerunisa et al (2016). Sebelumnya, SLCCNV pertama kali dilaporkan menginfeksi tanaman labu (Cucurbita pepo) di Pakistan (Tahir et al 2010) dan sampai saat ini telah menyebar ke Malaysia, Cina, Vietnam, Filipina, India, dan Thailand (CABI 2014).…”
Section: Pendahuluanunclassified
“…Mungbean yellow mosaic India virus merupakan anggota Begomovirus yang ditularkan melalui serangga vektor, yaitu kutukebul Bemisia tabaci Gen. (Hemiptera: Aleyrodidae) secara persisten sirkulatif (Hull 2014). Selain pada tanaman kacang panjang, beberapa anggota Begomovirus dilaporkan menyebabkan penyakit pada tanaman budi daya lainnya maupun gulma di Indonesia, diantaranya cabai, tomat, gulma Ageratum conyzoides, tembakau, terung dan mentimun (Rusli et al 1999, Hidayat et al 2002Haerani et al 2003;Hidayat et al 2008;Kintasari et al2013;Wiratama et al 2015). Oleh karena itu, perlu dilakukan deteksi dan identifikasi untuk membuktikan gejala mosaik kuning pada tanaman kedelai terinfeksi virus dari kelompok Begomovirus, untuk mencegah terjadinya epidemi dan pengendalian penyakit tersebut.…”
unclassified